ORE-BEARING MAGMATISM AT THE ERMAKOV BERYLLIUM DEPOSIT IN THE WESTERN TRANSBAIKAL REGION: AGE, MAGMA SOURCES, AND RELATIONSHIPS TO ORE MINERALIZATION - Lykhin D.A.; Kovalenko V.I.; Yarmolyuk V.V.; Kostitsyn Yu.A.; Sal'nikova E.B.; Kotov A.B.; Kovach V.P.; Ripp G.S. (My University, 2001)
We have determined the Rb-Sr isotopic ages of magmatic rocks and ores from the Ermakov deposit and established the following succession of formation from the early to the late stages: (1) formation of the host rocks represented by crystalline schists, sandstones, and dolomites; (2) the preore stage, which includes the formation of gabbroids (318 ± 2 Ma), fine- to medium-grained granites (283 ± 30 Ma), and gneissic granites with a U-Pb zircon age of (261 ± 5 Ma); (3) the synore magmatic stage, which includes the formation of basites, syenite-granites, and alkaline granites (255 ± 5 Ma); phlogopite micaites (255 ± 1, Ma); vesuvian skarns and ore bodies; and leucogranites of the Shtok massif (224 ± 1 Ma). Felsic dike formation was attributed to the postore stage. Field and isotopic studies showed that Be mineralization of the Ermakov deposit was genetically related to the association of rocks represented by basites, syenites, and alkaline granites; salt melts and brines (including carbonatite-like) also took part in the Be mineralization. Magmatic and ore-forming processes at the Ermakov deposit, as well as the formation of grabens and dike swarms in this region, were related to intracontinental rifting due to the early Mesozoic Central Asian mantle plume.
Keywords: Mesozoic; Transbaikal Region; Mesozoic; Мезозой